Rancang Bangun Distribusi Sock Coca Cola Berbasis Web (Studi Kasus PT. Coca Cola Amatil Surabaya) - Febriantono, Benny; Sukmaaji, Anjik; Taufik, Vicky M. (Jurnal JSIKA, 2012)
Distribution are economic activity that bridge between production and consumption activity. In order to keep soft drink stock in each outlets, PT. Coca Cola Amatil Surabaya Branch Office do checking and adding stock in each outlets once a week.All this time, distribution officer often to bring back the load to distributor because of amount that they bring are exceed the outlet needs, or the types of goods offered was not fit with outlets needs. Moreover, issue will appear due to track choosing that innefective did by the distribution officer. Evenmore, with chose wrong track, there are possibility that few outles will be missed.One solution to overcome those obstacles are to make web based distribution application for Coca Cola. This web application will be build using PHP language. Through those application, admin can easily monitor distribution process and transaction did every single day. Keyword: Stock distribution, Nearest route, Cheapest Insertion Heuristic, Web Application.